The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1987
DOI: 10.1104/pp.84.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in Situ and in Vitro Regulation of Soybean Seed Growth and Development

Abstract: The growth characteristics of soybean (Glycine max [L.] Merr.) embryos in culture and seeds in situ were found to be similar, but developmental differences were observed. Embryos placed in culture when very small (<2 milligrams dry weight) failed to attain the maximal growth rates attained by embryos which were more mature when placed in culture. When nutrient levels were maintained in the culture medium, embryos continued to grow indefinitely, reaching dry weights far in excess of seeds matured in situ. Appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Jang et al (2001) reported that application of asparagine in cell suspension medium had greater effect on formation of embryogenic clumps. Likewise, many researchers emphasised the addition of glutamine during embryo development mainly to increase the size of the embryos (Dyer et al 1987;Lippmann and Lippmann 1993). Previously, in soybean, these two amino acids were tested only in cell suspension cultures i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Jang et al (2001) reported that application of asparagine in cell suspension medium had greater effect on formation of embryogenic clumps. Likewise, many researchers emphasised the addition of glutamine during embryo development mainly to increase the size of the embryos (Dyer et al 1987;Lippmann and Lippmann 1993). Previously, in soybean, these two amino acids were tested only in cell suspension cultures i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Across seven genotypes, the in vitro growth rate of cultured cotyledons accounted for their in situ growth rates indicating that growth and hence solute transport was under cotyledon control (Dyer et al 1987). These conclusions are supported by the findings that both the in vitro (Hanson 1988) and in vivo (Hanson 1986) sucrose fluxes from the coats of developing soybean seed were not correlated with seed growth rates.…”
Section: Coarse Controlmentioning
confidence: 64%
“…For grain legume seed, the in vivo supply of assimilates to the outer surfaces of the cotyledons (Patrick and McDonald 1980;McDonald et al 1995c) can be reproduced readily in vitro by incubating excised cotyledons in a culture solution (Litchner and Spanswick 1981a;Patrick 1981;Dyer et al 1987;McDonald et al 1 9 9 5~;see Fig. 2b).…”
Section: Experimental Systemsmentioning
confidence: 99%
“…Studies of zygotic soybean and bean (Phaseolus vulgaris) embryos cultured in vitro suggest that seed growth rate and maturation are controlled by the embryo (TeKrony et al 1979;Adams and Rinne 1981;Egli et al 1981;Dyer et al 1987), and parallel that of embryos in planta (Long et al 1981). Studies of zygotic soybean and bean (Phaseolus vulgaris) embryos cultured in vitro suggest that seed growth rate and maturation are controlled by the embryo (TeKrony et al 1979;Adams and Rinne 1981;Egli et al 1981;Dyer et al 1987), and parallel that of embryos in planta (Long et al 1981).…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%